List checking evaluation of children's software collection at Woodlands Regional Library. - Heng, Huey Bin. (2008)
The study concentrates on evaluating the scope, quality, and usefulness of the software collection for children and at the same time, seeks to discover the collection strengths and weaknesses of these areas. It is also the objective of the study to find out if emphasis has been given to the software collection for children using the chi-square "goodness of fit" test of a tiered checklist.